An examination of the right of women to inherit land as seen in Numbers 27:1-11; 36:1-12; Joshua 17:1-6, and Job 42:14-15; and its relevance and application to the traditions and present situation of the Toba Batak Samosir community in Indonesia - Sinaga, Debora Purada ([n.p.] : South East Asia Graduate School of Theology, 2000)
Toba Batak Samosir women in Indonesia currently face a critical situation of inequality in inheriting land as they enter the 3rd millennium. This matter has been a lingering socio-political economic issue in the Christian communities in Indonesia. These women have appeared in the front lines demanding legislative equality to inherit land. Many women have shown resistance unto death, and were killed as they stood up to defend their rights. Women argue they should be able to inherit land on their own right, and that only they should decide what the land is to be used for, as in cultivation of crops that others may live
This thesis attempts to demonstrate that there is biblical justification for women to inherit land [Numbers 27:1-11; 36:1-12; Joshua 17:1-6 and Job 42:14-15]
In partial fulfillment of the requirements for the Degree of Master of Theology
A thesis presented to the Faculty of the South East Asia Graduate School of Theology (SEAGST).
Thesis (M. Theo)- The Divinity School, Siliman University